TO DESIGN AND BUILD OF A SURVEILLANCE/ATTACK MINI UNMANNED AERIAL VEHICLE (UAV) - A.Serkan AKGÜL; Abdurrahman HACIOĞLU (Havacılık ve Uzay Teknolojileri Dergisi, 2010)
In this study, it is aimed to analyze an unmanned air vehicle (UAV) design parameters, to finish design calculations and aerodynamic and performans calculations. Therefore, this study helps UAV works carried out within the Turkish Air Force Academy undergraduate and graduate training programs. Within the study, the goal is to design and build a propeller driven, electric powered, unmanned “Surveillance and Attack” R/C airplane which is capable of flying three predefined missions: Ferry Flight, Surveillance Flight and Stores Release/Asymmetric Loads Flight.So, in the design phase, so many package programs are used to obtain visual details. In manufacturing phase, TUAF (Turkish Air Force Academy), ITU (Istanbul Technical University) and Baykar Machinarys’ all opportunities and capabilities were benefitted from.